The imperative of international cooperation for EU competitiveness and resilience in technology-driven industries - Matthias Bauer; Renata Zilli; Dyuti Pandya (European Centre for International Political Economy (ECIPE), 2023)
The EU must embrace international cooperation and collaboration in technology-driven industries to ensure competitiveness and global relevance, while also considering the drawbacks of isolationist policies. The EU's commitment to open markets and global cooperation has historically been its strength, and EU policymakers should continue to prioritise on these principles. Global markets, international R&D collaboration and global industry-led standards are crucial for innovation and efficiency in technology-intensive industries. Various sectors, including pharmaceuticals, ICT, aerospace, and defence, heavily rely on global partnerships to stay competitive and advance technologically. International cooperation in economic and security affairs, as exemplified by EU participation in global value chains of advanced semiconductors, the traditional EU approach to industry-led technology standardisation, and EU involvement in the international F-35 fighter development program, is critical for leveraging industry expertise, sharing technological advancements, and collectively addressing challenges in strategic sectors, thereby enhancing Europe's economic resilience and security capabilities. Trust and legal certainty form the foundation for international partnerships in high-tech and defence sectors. Collaborations among like-minded partners enable secure information sharing, intellectual property protection, financial commitments, and compliance with regulations, while ensuring adherence to key EU values like human rights and the rule of law.
Keywords: 330; Location competition; International business cooperation; Standardization; EU foreign trade policy; EU research policy; ICT sector; Pharmaceutical industry; Aviation industry; Standortwettbewerb; Internationale Unternehmenskooperation; Standardisierung; EU-Außenwirtschaftspolitik; EU-Forschungspolitik; IKT-Sektor; Pharmaindustrie; Luftfahrtindustrie